Exploring the Molecular Basis for Substrate Affinity and Structural Stability in Bacterial GH39 β-Xylosidases - Morais, Mariana Abrahão Bueno de; Polo, Carla Cristina; Domingues, Mariane Noronha; Persinoti, Gabriela Felix; Pirolla, Renan Augusto Siqueira; de Souza, Flávio Henrique Moreira; Correa, Jessica Batista de Lima; dos Santos, Camila Ramos; Murakami, Mário Tyago (Frontiers in Bioengineering and Biotechnology, 2020)
The glycoside hydrolase family 39 (GH39) is a functionally expanding family with limited understanding about the molecular basis for substrate specificity and extremophilicity. In this work, we demonstrate the key role of the positive-subsite region in modulating substrate affinity and how the lack of a C-terminal extension impacts on oligomerization and structural stability of some GH39 members. The crystallographic and SAXS structures of a new GH39 member from the phytopathogen Xanthomonas citri support the importance of an extended C-terminal to promote oligomerization as a molecular strategy to enhance thermal stability. Comparative structural analysis along with site-directed mutagenesis showed that two residues located at the positive-subsite region, Lys166 and Asp167, are critical to substrate affinity and catalytic performance, by inducing local changes in the active site for substrate binding. These findings expand the molecular understanding of the mechanisms involved in substrate recognition and structural stability of the GH39 family, which might be instrumental for biological insights, rational enzyme engineering and utilization in biorefineries.